2015
DOI: 10.5966/sctm.2015-0157
|View full text |Cite|
|
Sign up to set email alerts
|

Naïve Induced Pluripotent Stem Cells Generated From β-Thalassemia Fibroblasts Allow Efficient Gene Correction With CRISPR/Cas9

Abstract: Conventional primed human embryonic stem cells and induced pluripotent stem cells (iPSCs) exhibit molecular and biological characteristics distinct from pluripotent stem cells in the naïve state. Although naïve pluripotent stem cells show much higher levels of self-renewal ability and multidifferentiation capacity, it is unknown whether naïve iPSCs can be generated directly from patient somatic cells and will be superior to primed iPSCs. In the present study, we used an established 5i/L/FA system to directly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 29 publications
(47 reference statements)
2
51
0
1
Order By: Relevance
“…A recent study reported efficiency of CRISPR/Cas9 system for correction of HBB in iPSCs|: up to 57% of the clones showed modification of at least one HBB allele in experimental series, as well as minimal off-target activity [28].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…A recent study reported efficiency of CRISPR/Cas9 system for correction of HBB in iPSCs|: up to 57% of the clones showed modification of at least one HBB allele in experimental series, as well as minimal off-target activity [28].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Этот подход уже был использован в экспериментах по коррекции мутаций, вызы-вающих тяжелые наследственные болезни (му-ковисцидоз [15], миодистрофия Дюшенна [16], дегенерация сетчатки глаза [17]), для лечения инфекционных заболеваний (вИЧ) [18] и в ис-следованиях тонкой структурно-функциональ-ной организации генома человека. Недавно с помощью этой технологии были проведены эксперименты на мышах, а затем на зиготах че-ловека для коррекции мутаций гена β-глобина, вызывающих тяжелое и частое наследственное заболевание -β-талассемию [19]. Результаты этих экспериментов вызвали большой науч-ный резонанс.…”
Section: достижения вспомогательных репродуктивных технологий и новыеunclassified
“…Precisely engineered iPSCs are needed for stem cell-based modelling of genetic disease, and for providing an unlimited source of gene-edited lines for potential use in regenerative medicine [228,229]. Recent studies have reported successful gene correction of beta thalassaemia mutations using Cas9WT in iPSCs [35][36][37]138]. Cooperative strategies, (i.e.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…While the generation of iPSCs from the fibroblasts of beta thalassaemia individual [26][27][28][35][36][37] and amniotic fluids cells [38] has previously been reported [28,187] he production of footprint-free iPSCs from fibroblasts derived from patients with the Mediterranean mutation IVSII-1(G>A) of beta thalassaemia has not been reported to date (Table1-1). IVSII-1(G>A) is a splice junction mutation that affects the 5′ splice site leading to a severe form of beta thalassaemia in the homozygous state.…”
Section: Excision Of the Selection Cassettementioning
confidence: 99%
See 1 more Smart Citation